Prevalence of skin tears among hospitalized patients with cancer - Amaral, Ana Flávia dos Santos; Pulido, Kelly Cristina Strazzieri; Santos, Vera Lucia Conceição de Gouveia (Revista da Escola de Enfermagem da USP, 2012)
This study aimed to analyze the prevalence of skin tears (ST) among hospitalized oncology patients and associated demographic and clinical variables. This is an epidemiological cross-sectional study type, performed at Octavio Frias de Oliveira State of São Paulo Cancer Institute. All adult patients hospitalized from April 10th to 18th 2010 were evaluated by interview and physical examination. Chi-square test was used to compare demographic and clinical variables between patients with and without ST. Five patients among 157 had nine skin tears, resulting in a prevalence of 3.3%. Among demographic variables, only number of children showed statistically significant difference (p=0.027) between groups. Clinically, patients with ST had lower Karnofsky scores (p=0.031), lower scores at Braden Scale (p=0.026) and less collaborative behaviors (p=0.042) when compared to patients with no lesions. This study contributes to a better knowledge of ST in oncology patients.